Probucol-Oxidized Products, Spiroquinone and Diphenoquinone, Promote Reverse Cholesterol Transport in Mice. Issue 4 (April 2016) - Yakushiji, Emi; Ayaori, Makoto; Nishida, Takafumi; Shiotani, Kazusa; Takiguchi, Shunichi; Nakaya, Kazuhiro; Uto-Kondo, Harumi; Ogura, Masatsune; Sasaki, Makoto; Yogo, Makiko; Komatsu, Tomohiro; Lu, Rui; et al.
Abstract : Objective—: Oxidized products of probucol, spiroquinone and diphenoquinone, were shown to increase cell cholesterol release and plasma high-density lipoprotein (HDL) by inhibiting degradation of ATP-binding cassette transporter A1. We investigated whether these compounds enhance reverse cholesterol transport in mice. Approach and Results—: Spiroquinone and diphenoquinone increased ATP-binding cassette transporter A1 protein (2.8- and 2.6-fold, respectively, P <0.01) and apolipoprotein A-I–mediated cholesterol release (1.4- and 1.4-fold, P <0.01 and P <0.05, respectively) in RAW264.7 cells. However, diphenoquinone, but not spiroquinone, enhanced cholesterol efflux to HDL (+12%, P <0.05), whereas both increased ATP-binding cassette transporter G1 protein, by 1.8- and 1.6-fold, respectively. When given orally to mice, both compounds significantly increased plasma HDL-cholesterol, by 19% and 20%, respectively ( P <0.05), accompanied by an increase in hepatic and macrophage ATP-binding cassette transporter A1 but not ATP-binding cassette transporter G1. We next evaluated in vivo reverse cholesterol transport by injecting RAW264.7 cells labeled with 3 H-cholesterol intraperitoneally into mice. Both spiroquinone and diphenoquinone increased fecal excretion of the macrophage-derived 3 H-tracer, by 25% and 28% ( P <0.01 and P <0.05), respectively. spiroquinone/diphenoquinone did not affect fecal excretion of HDL-derived 3 H-cholesterol, implying that macrophage-to-plasma was the most important step in spiroquinone/diphenoquinone-mediated promotion of in vivo reverse cholesterol transport. Finally, spiroquinone significantly reduced aortic atherosclerosis in apolipoprotein E null mice when compared with the vehicle. Conclusions—: Spiroquinone and diphenoquinone increase functional ATP-binding cassette transporter A1 in both the macrophages and the liver, elevate plasma HDL-cholesterol, and promote overall reverse cholesterol transport in vivo. These compounds are promising as therapeutic reagents against atherosclerosis. Abstract : Supplemental Digital Content is available in the text.